A Case of Drug-Induced Liver Injury Secondary to Natalizumab - Phillip P. Santoiemma; Haripriya Maddur; Christopher M. Moore (Case Reports in Hepatology)
A 33-year-old Caucasian female with relapsing-remitting multiple sclerosis presented with abdominal pain, nausea, and vomiting and was found to have acute liver injury. After thorough investigation, she was diagnosed with drug-induced liver injury (DILI) thought secondary to redosing of Natalizumab therapy.